Pengaruh Gaya Kepemimpinan, Knowledge Management Dan Keterampilan Terhadap Kinerja Anggota Kepolisian Direktorat Reserse Kriminal Umum Polda Sumbar - Rezki, Rezki; Lucy Chairoel (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to determine the influence of leadership style, knowledge management and skills on the performance of police members of the West Sumatra Regional Police General Criminal Investigation Directorate. Leadership Style is behavior and strategy as a result of a combination of philosophies, skills, traits and attitudes that a leader often applies as he tries to influence the satisfaction of his subordinates. Knowledge Management is information about a particular field by a person. Therefore, Knowledge Management can be developed through formal and informal education. Skills are the capacity needed to carry out several tasks which are the development of the training results and experience gained. In addition to the training needed to develop skills, skills also require basic skills (basic obility) to do work easily and appropriately. Performance is a means of managing an agency that aims to achieve decision-making and accountability. The object of this research was carried out at the Directorate of General Criminal Investigation of the West Sumatra Police. The method used in this study is a quantitative method, the number of population and the number of samples in this study are all members of the Directorate of General Criminal Investigation of the West Sumatra Police totaling 60 people with sampling techniques using saturated sampling techniques (census). The data collection method uses the observation method and the distribution of questionnaires with Likert scale measurements. The data analysis techniques in this study are research instrument tests, classical assumption tests, multiple linear regression analysis and hypothesis tests using the SPSS version 22 program. The results of hypothesis testing in this study show that 1) leadership style partially has a positive and significant effect on performance, 2) knowledge management partially has a positive and significant effect on performance, 3) skills simultaneously have a positive and significant effect on performance, 4) leadership style, knowledge management, and skills simultaneously have a positive and significant effect on performance.